Lessons from the Green Lanes: Evaluating Protected Bike Lanes in the U.S. Final report. - (:unkn) unknown (My University, 2014)
As cities move to increase levels of bicycling for transportation, many practitioners and advocates have promoted the use of protected bike lanes (also known as "cycle tracks" or "protected bikeways") as an important component in providing high-quality urban infrastructure for cyclists. These on-street lanes provide more space and physical separation between the bike lane and motor vehicle lane compared with traditional striped bike lanes. However, few U.S. cities have direct experiences with their design and operations, in part because of the limited design guidance provided in the past. There is limited research from North America on protected bike lanes, but preliminary evidence suggests that they can both improve the level of comfort of cyclists and potentially increase the number of people cycling. This research evaluates protected bike lanes in five distinct contexts varying in population, driving and cycling rates and cultures, and weather: Austin, Texas; Chicago, Illinois; Portland, Oregon; San Francisco, California; and, Washington, District of Columbia. These five cities participated in the inaugural "Green Lane Project" (GLP) sponsored by People for Bikes (formerly known as Bikes Belong). This evaluation focused on six questions: - Do the facilities attract more cyclists? - How well do the design features of the facilities work? In particular, do both the users of the protected bicycle facility and adjacent travel lanes understand the design intents of the facility, especially unique or experimental treatments at intersections? - Do the protected lanes improve users' perceptions of safety? - What are the perceptions of nearby residents? - How attractive are the protected lanes to different groups of people? - Is the installation of the lanes associated with measurable increases in economic activity?
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Verkehrssicherheit; Verkehrsplanung; Radverkehrsanlage; Fahrradinfrastruktur; Radverkehrsplanung; Radverkehrsführung; Radverkehrssicherheit; Studie; Befragung; Konfliktvermeidung; Protected Bike Lane